Proposals for the future: physical structure and the ideal team for psychiatric emergencies - Kawakami, Daniel (2016)
Currently, psychiatric emergency services play a key role in the Brazilian network of mental health services. The outcome of acute psychiatric conditions often depends on the performance of these services. This article presents concepts and general information on psychiatric emergency services, including Brazilian and worldwide perspectives, and analyzes trends and proposals on planning measures and service structuring. Experiences and models are analyzed as possibilities for changes in psychiatric emergency services. In conclusion, the authors reinforce the importance of articulating and effectively implementing priorities in the organizationof psychiatric emergency services in the context of the Brazilian public Unified Health System.